(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
This article provides detailed information about the history of the formation of musical culture in the Arab nations, the stages of development of musical culture in the Arabs and their analysis, the activities of performance schools, and the analysis of musical genres in the works of scientists.